The PROMISE study protocol: a multicenter prospective study of process optimization with interdisciplinary and cross-sectoral care for German patients receiving hip and knee endoprostheses. - Betz, Ulrich; Langanki, Laura; Heid, Florian; Spielberger, Jan; Schollenberger, Lukas; Kronfeld, Kai; Büttner, Matthias; Büchler, Britta; Goldhofer, Markus; Eckhard, Lukas; Drees, Philipp (Acta Orthopaedica, 2021)
Background and purpose — Knee and hip replacement are common and increasing procedures, and an optimized care process that could be implemented in different settings would be useful. The PROMISE trial investigates whether a new care process works equally in different German settings and how the results compare with current non-standardized care. Patients and methods — This multi-center prospective mixed-method study includes 2,000 German patients receiving arthritis-related hip or knee endoprostheses. An interdisciplinary and cross-sectoral care process was developed and implemented in 3 German hospitals with different levels of care, and corresponding rehabilitation centers were included to bridge the gap after acute care. Duration and outcome — The PROMISE trial recruited patients between May 2018 and March 2020. Follow-up will end in February 2021. Assessments are performed at: examination on clinical indication, 1 week before surgery, on the day of surgery, at the end of hospitalization, end of the rehabilitation program, and 3 months, 6 months, and 12 months after surgery. Outcomes include patient-reported outcomes, medical examination findings, and routinely collected data regarding the surgery and complications. Guideline-based interviews are conducted with selected patients and care partners. The primary endpoint is the presence of chronic pain at 12 months after surgery. Secondary endpoints are the number of recognized pre-existing conditions, physical activity at 12 months after surgery, use of medical services, quality of life, and interactions between care partners. Trial registration — The trial is registered with the German Clinical Trials Register (; DRKS00013972; March 23, 2018).